Genotypes of Cryptosporidium spp., Enterocytozoon bieneusi and Giardia duodenalis in dogs and cats in Shanghai, China. Issue 1 (December 2016) - Xu, Hailing; Jin, Yue; Wu, Wenxian; Li, Pei; Wang, Lin; Li, Na; Feng, Yaoyu; Xiao, Lihua
Abstract Background Controversies exist on the potential role of companion animals in the transmission of enteric pathogens in humans. This study was conducted to examine the genotype distribution ofCryptosporidium spp., Enterocytozoon bieneusi, andGiardia duodenalis in companion animals in Shanghai, China, and to assess their zoonotic potential. Methods Fecal specimens from 485 dogs and 160 cats were examined for the occurrence and genotype distribution of the three pathogens by PCR. PCR products were sequenced to determine the species and genotypes. The χ2 test was used to compare differences in infection rates between living conditions or age groups. Results Cryptosporidium spp., E. bieneusi andG. duodenalis were found in 39 (8.0 %), 29 (6.0 %) and 127 (26.2 %) of dogs, and 6 (3.8 %), 9 (5.6 %) and 21 (13.1 %) of cats, respectively. Infection rates of the pathogens in dogs from pet shops and a clinic were higher than those in household dogs, and higher in cats from one animal shelter than from pet shops. No significant differences in infection rates were detected among age groups.Cryptosporidium canis andC. felis were the onlyCryptosporidium species found in dogs and cats, respectively.Enterocytozoon bieneusi genotype PtEb IX was the dominant genotype in dogs, whereas Type IV and D were the most common ones in cats. Multi-locus sequence typing at the glutamate dehydrogenase, β-giardin, and triosephosphate isomerase loci revealed the presence ofG. duodenalis assemblages A (n  = 23), B (n  = 1), C (n  = 26), and D (n  = 58) in dogs (only A in household dogs) and assemblages A (n  = 2), B (n  = 6), C (n  = 2), D (n  = 1), and F (n  = 7) in cats. Co-infection was detected in 24 dogs and 5 cats, especially those living in crowded conditions. Conclusions Living condition is a major risk factor affecting the occurrence of enteric protists in companion animals in China, and although dogs and cats can be potential sources of human infections, the different distribution of pathogen species and genotypes between dogs and cats suggests that inter-species transmission of these pathogens is probably rare in the study area.